Perancangan Sistem Presensi dengan RFID Berbasis Website: PERANCANGAN SISTEM PRESENSI DENGAN RFID BERBASIS WEBSITE - sudiana; Wahyu Eko Prasetyo; Arif Basuki; Joko Prasojo; Dwika Nove Rahmanto (Retii, 2022)
The attendance system is an important aspect because it records attendance and recaps data which can later be used as reports or aspects of student assessment. However, the attendance system used today is still paper-based where students sign it according to the column/row of their name. Therefore, the presence system that will be designed in this study uses RFID (Radio Frequency Identification) technology. The system is made using an ESP-32 microcontroller, FRC522 RFID reader, RFID tag, 16x2 LCD, buzzer, TP4056 lithium ion battery charger, and 18650 battery. The LCD will display a presence message, if there is a UID number in the database it will be stored and displayed on the website page, but if it is not there a message will appear that the UID number is not on the LCD screen. The results of the study show the system works well, this is indicated by a system that can facilitate and speed up the attendance recapitulation process because the attendance data results are already stored in the database and can be retrieved in pdf and excel form on the website page Keyword : RFID, website, database, attendance